Metagenomic and metatranscriptomic responses of natural oil degrading bacteria in the presence of dispersants. (25th April 2019) - Tremblay, Julien; Fortin, Nathalie; Elias, Miria; Wasserscheid, Jessica; King, Thomas L.; Lee, Kenneth; Greer, Charles W.
Summary: Oil biodegradation has been extensively studied in the wake of the deepwater horizon spill, but the application of dispersant to oil spills in marine environments remains controversial. Here, we report metagenomic (MG) and metatranscriptomic (MT) data mining from microcosm experiments investigating the oil degrading potential of Canadian west and east coasts to estimate the gene abundance and activity of oil degrading bacteria in the presence of dispersant. We found that the addition of dispersant to crude oil mainly favours the abundance of Thalassolituus in the summer and Oleispira in the winter, two key natural oil degrading bacteria. We found a high abundance of genes related not only to n ‐alkane and aromatics degradation but also associated with transporters, two‐component systems, bacterial motility, secretion systems and bacterial chemotaxis.